Catalase Activity in Anaplasma marginale - Wallace, W. R. (1965)
Wallace, W. R. (Louisiana State University, Baton Rouge), and G. T. Dimopoullos. Catalase activity in Anaplasma marginale. J. Bacteriol. 91:309–311. 1965.—Extracts of erythrocytes infected with Anaplasma marginale were found to contain more catalase activity than normal erythrocytic preparations. The increase in catalase activity appeared concurrently with increases in the number of erythrocytes containing Anaplasma bodies. Antisera against normal bovine erythrocytes and Anaplasma-infected erythrocytes were prepared in rabbits to test the source of increased catalase activity during anaplasmosis. Antiserum against normal erythrocytes decreased the catalase activity of extracts of normal erythrocytes by 271 units per ml and of partially purified Anaplasma bodies by only 120 units. Rabbit antiserum against Anaplasma-infected bovine erythrocytes removed only 73 units of activity from normal erythrocytes, but decreased the activity of the partially purified Anaplasma bodies by 260 units, indicating the association of catalase with the marginal body.